Uma análise das relações dialógicas nas notícias sobre a greve dos professores em 2015 - Mateus, Karen Lís Ferreira (2017)
In order to investigate the ideological positions in the journalistic sphere, this paper analyzes some statements published during the teachers' strike in the State of São Paulo, which began on March 13 and ended on June 12, 2015. It is considered, therefore, the relevance of the material produced by the news media in the composition of the facts. Interest to research the constitution of the news genre in the newspaper O Estado de São Paulo and Folha de São Paulo to observe how the thematic content developed as well as the statements strategies of each newspaper reveals its intentions and ideological values. It is considered in the corpus of the analysis, discourses that create the statements of the news and how dialogical relations are raised in them. The newspapers reveal, from the selections made, strike events every day and bring the highlights of the day, according to their interests, which may diversify depending on the ideology of each newspaper company, so the understanding of each newspaper can vary manner to privilege one subject over another. The thought of Bakhtin (2015) and studies of Brait (2007), Faraco (2009), Stella (2007), among other researchers from the philosopher, give theoretical support to this study, therefore they allow us to investigate how the language is manifested in the event dialogic between the subjects and verify to what extent it is necessary to recognize the other as an active participant of human existence. The reflections developed by the Russian philosopher M. Bakhtin offer paths that give us clues about to the way in which subject participates in the act of communication. Following these paths, it is observed that the statements from both newspapers established themselves in the interaction of subjects, whose responsive actions do not address the teachers' strike in the State of São Paulo as a manifestation of the category, but as a partisan and political movement. Thus, the research is carried out from the analysis of the subject, the language and the media, as well as the interrelation between them in the environment around them.